Atorvastatin: old friend in the light of novel coronavirus infection’s pandemia - M. V. Ezhov; T. E. Kolmakova; M. M. Matveeva; I. A. Alekseeva (Медицинский совет, 2022)
The COVID-19 (COronaVIrus Disease 2019) pandemic caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome CoronaVirus 2) continues to be a global threat to people and health systems. As of March 21, 2022, there are more than 460 million cases and more than 6 million deaths worldwide, and more than 17 million and 360,000 respectively in the Russian Federation. Due to the rapid spread of the new coronavirus infection, since the beginning of the pandemic, tremendous efforts have been made to create new pharmacological agents to reduce morbidity and mortality, and tactics have been used to repurpose existing medications in treatment regimens for patients with COVID-19, particularly statins. Statins represent one of the most widely used and prescribed classes of drugs in the world. The hypolipidemic properties of statins are actively used to treat hyperlipidemia and primary and secondary prevention of cardiovascular diseases and their complications. Statins have a known safety profile, are inexpensive and accessible. In addition to their hypolipidemic effects, statins have a wide range of pleiotropic anti-inflammatory, antiviral, and antithrombotic effects potentially useful in the treatment of COVID-19. Presumably, the use of statins can reduce SARS-CoV-2-induced organ and tissue damage and improve lung function. The use of statins, particularly atorvastatin, as one of the most effective, widely prescribed and studied drugs in this class, as a safe, affordable and relatively inexpensive therapy may be a promising therapeutic approach in the fight against a new coronavirus infection.